Edukasi Tentang Pendidikan Seksual pada Anak Sekolah - Maria Tarisia Rini; Ketut Suryani; Bangun Dwi Hardika; Sri Indaryati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Children are individuals who are still very innocent and have not been able to distinguish between the words of parents or sexual harassment. Considering that many cases of sexual harassment are committed by people closest to the child who should be the protector of the child. The family is the school or the initial foundation of a child, therefore sexual education should be given by the family to the child since the child has begun to be able to speak or since toddler age. But in reality there are still many children who don't even know the names of their body parts, which body parts can and cannot be held by others. This service aims to provide an understanding to children about the names of their body parts including the names of their genitals and provide an understanding of body parts that can and cannot be held by others, and what to do when someone else will hold their private area. This educational activity begins with planning, implementing activities and evaluation. Based on the results of the activity, it was found that after the educational activities were carried out, children understood which areas of the body could and could not be held by others and ran to ask for help from others when someone would hold their private areas.